Legal Issues in the Oversight and Enforcement of Advocate Professional Ethics in Indonesia - Rosdiana; Arda, Ravi; Yanti, Desi (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
The oversight and enforcement of the advocate code of ethics in Indonesia continue to face various challenges, affecting the effectiveness of existing regulations. The number of ethical violations among advocates has increased significantly, rising from 120 cases in 2018 to 345 cases in 2023. The most common infractions include conflicts of interest, abuse of authority, and gratuities. One of the primary factors contributing to weak ethical enforcement is the current oversight system, which remains limited to advocate organizations without the involvement of an independent regulatory body. This study aims to analyze the effectiveness of advocate oversight mechanisms in Indonesia, compare them with best practices in other jurisdictions, and identify measures to enhance accountability and transparency in the legal profession. The research employs a normative legal method with a comparative law approach and empirical studies. The analysis includes an examination of existing regulations, case reports on ethical violations, and interviews with key stakeholders, including advocates, clients, and legal analysts. The findings indicate that only 40% of reported violations result in strict sanctions, while only 10% of advocates found guilty of ethical breaches face license revocation. Additionally, a survey of 500 respondents reveals that only 35% of the public is aware of the procedures for filing complaints against unethical advocates, highlighting a lack of transparency in the oversight system. This study contributes to the discourse by recommending the establishment of an independent regulatory body to monitor advocate compliance with ethical standards and the enhanced utilization of digital technology in the oversight system. With more transparent and accountable regulatory reforms, ethical violations within the legal profession can be minimized, ultimately strengthening public trust in Indonesia’s legal system.